2022
DOI: 10.1097/gox.0000000000004328
|View full text |Cite
|
Sign up to set email alerts
|

Practical Review of the Cost of Diagnosis and Management of Positional Plagiocephaly

Abstract: Background: Positional plagiocephaly has garnered increased research interest since the introduction of the Back to Sleep campaign in the 1990s, and the subsequent increase in infants with cranial deformity. Research has focused on treatment outcomes and developing new modalities to address asymmetric heads. Little attention has been given to the cost of treatment and diagnosis. This study aimed to summarize the literature and provide an overview of the costs associated with a diagnosis of position… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Theoretical cost models estimate the individual cost of diagnosis and treatment of plagiocephaly between $1495 to more than $5000 depending on timing of diagnosis with diagnosis after 6 months incurring the most cost. 15 We found that parental education at the newborn visit led to decreases in CI at 2 and 4 months compared with control patients, which is relevant as this seems to be the ideal timing for intervention. In summary, we would expect to see a reduction in physician visits, referring surgeons' time, and helmeting therapy among the target population with the addition of plagiocephaly education to the current Back to Sleep lexicon.…”
Section: Significancementioning
confidence: 53%
See 1 more Smart Citation
“…Theoretical cost models estimate the individual cost of diagnosis and treatment of plagiocephaly between $1495 to more than $5000 depending on timing of diagnosis with diagnosis after 6 months incurring the most cost. 15 We found that parental education at the newborn visit led to decreases in CI at 2 and 4 months compared with control patients, which is relevant as this seems to be the ideal timing for intervention. In summary, we would expect to see a reduction in physician visits, referring surgeons' time, and helmeting therapy among the target population with the addition of plagiocephaly education to the current Back to Sleep lexicon.…”
Section: Significancementioning
confidence: 53%
“…Plagiocephaly is associated with significant health care costs, making prevention of particular importance. Theoretical cost models estimate the individual cost of diagnosis and treatment of plagiocephaly between $1495 to more than $5000 depending on timing of diagnosis with diagnosis after 6 months incurring the most cost 15 . We found that parental education at the newborn visit led to decreases in CI at 2 and 4 months compared with control patients, which is relevant as this seems to be the ideal timing for intervention.…”
Section: Discussionmentioning
confidence: 81%
“…Conversely, a positive trend in cranial symmetry after at-home implementation of additional tummy time and physiotherapy may indicate a resolving plagiocephaly requiring monitoring but no additional consultation. 11,29 Recent events have highlighted an urgent need for improved modalities to provide adequate care remotely with telemedicine. 30,31 Rizvi et al, alongside Marianayagam et al, have released studies evaluating the outcomes of virtual craniofacial clinics for the assessment of positional plagiocephaly based on standard digital images, concluding that virtual encounters resulted in comparable diagnostic accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, the authors demonstrated that earlier diagnosis is associated with better aesthetic outcomes, shorter treatment times, lower costs for treatment, a lower stress burden for parents, and lower costs for the healthcare system overall. 11 In large part, this is due to early detection maximizing the chance of successful intervention with repositioning and physical therapy, negating the need to progress to helmet therapy or, in extreme cases, surgery. 11 It is not surprising then that various techniques have been developed to accurately and efficiently diagnose head deformities in the pediatric population.…”
Section: Introductionmentioning
confidence: 99%
“…within the first weeks of life) (Ellwood et al, 2020). Indeed, when parents of newborns are made aware that prevention strategies exist, their babies are two to four times less likely to develop DP (Aarnivala et al, 2015; Cavalier et al, 2011; Lennartsson & Nordin, 2019; Leung et al, 2018), and the costs associated with diagnosis and treatment, which vary between $1495 and $5195 US, can be avoided (Watt et al, 2022).…”
Section: Introductionmentioning
confidence: 99%